LEVEL OF WORK-RELATED STRESS OF MEDICAL TECHNOLOGISTS IN PAMPANGA, BULACAN, BATAAN AND TARLAC DURING THE COVID-19 PANDEMIC - Camia, Jerome; Geroleo, Rei-Ann; Guillermo, Hannah Shayne; Icabandi, Jazmine Joyce; Manarang, Joemari; Martin, I, Gregorio (International Journal of Arts, Sciences and Education, 2021)
Work-related stress is an uncommon and long-standing concern among healthcare professionals worldwide. Studies have shown that this has worsened during the COVID-19 Pandemic and can directly affect the quality of healthcare delivery. Although numerous studies are continuously being published regarding this matter, only a few include medical technologists. Hence, this descriptive and correlational quantitative study is aimed at determining the most prevalent level of work-related stress of medical technologists in Pampanga, Bulacan, Bataan and Tarlac during the COVID-19 Pandemic, and its association with their demographic characteristics and handling of COVID-19 cases. Upon receipt of ethical clearance, data collection was conducted for three weeks. In determining the level of work-related stress, the study used a survey questionnaire developed by the Indian Council of Medical Research (ICMR). A total of 227 respondents were surveyed through Google Forms using snowball sampling technique. Subsequently, descriptive statistics, Spearman’s rank-order correlation and Chi-square test of independence (CI=95%, p=<0.05) were utilized for data analysis. Results showed that the majority of the respondents have a moderate level of work-related stress (66.52%). Furthermore, it was shown that stress at work is not significantly affected by the demographic characteristics of the respondents. However, results from the Chi-square test of independence revealed that it is significantly associated with the handling of COVID-19 tests and/or patients (p=0.0291). Because of this, the researchers recommended interventions that can be done to prevent such stress from worsening and progressing to burnout. Recognizing this problem can help prevent accidents in the laboratory and improve healthcare delivery.